2014
DOI: 10.3345/kjp.2014.57.10.451
|View full text |Cite
|
Sign up to set email alerts
|

Serum procalcitonin as a diagnostic marker of neonatal sepsis

Abstract: PurposeWe evaluated serum procalcitonin (PCT) as a diagnostic marker of neonatal sepsis, and compared PCT levels with C-reactive protein (CRP) levels.MethodsWe retrospectively reviewed the medical records of 269 neonates with a suspected infection, admitted to Wonkwang University School of Medicine & Hospital between January 2011 and December 2012, for whom PCT and CRP values had been obtained. Neonates were categorized into 4 groups according to infection severity. CRP and PCT values were analyzed and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…Park et al also demonstrated increased severity of infection with high procalcitonin concentrations [22]. This study showed that 0.5 mg/L is the best cut-off value of procalcitonin for diagnosing neonatal bacterial infection.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Park et al also demonstrated increased severity of infection with high procalcitonin concentrations [22]. This study showed that 0.5 mg/L is the best cut-off value of procalcitonin for diagnosing neonatal bacterial infection.…”
Section: Discussionmentioning
confidence: 80%
“…The role of procalcitonin concentration in predicting sepsis in patients of different age groups and in different conditions was studied by several authors such as Assicot et al [21][22][23][24]. Assicot et al showed that high procalcitonin concentrations were related to acute septic episodes in children, but the reference range used was different [21].…”
Section: Discussionmentioning
confidence: 99%
“…groups when compared with healthy controls (P< 0.05). Also some authors observed high concentrations of PCT during proved sepsis, [45,46] and comparable low concentrations in suspected sepsis. In a study by Guibourdenche et al [47], very low PCT concentrations were measured during SIRS, but high concentrations when sepsis was diagnosed.…”
Section: Discussionmentioning
confidence: 91%
“…A rapid test with the best degree of sensitivity, reliability, and predictability is required for the early diagnosis and treatment of neonatal sepsis [51]. From ROC curve at cut off CRP 9 mg/l the sensitivity and specificity were (72%, 61% respectively) which were less useful in diagnosis of neonatal sepsis compared to presepsin at cut off 500 pg/ml which has the highest sensitivity and specificity (95%, 81% respectively) followed by procalcitonin which at 5.6 ng/ml cut off had sensitivity and specificity (90%, 69% respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal urinary tract infection in the prenatal period is considered a risk factor for the occurrence of intra-amniotic infection, hypertension/preeclampsia, maternal anemia, premature labor, and low birth weight, highlighting the importance of urine examination antepartum [1,2]. McGrady et al observed that acute urinary tract infection during pregnancy was associated with fetal mortality in 17.9% of live births, and that early neonatal sepsis onset was of major concern [3]. Due to the lack of sufficiently sensitive or specific criteria for the early detection of neonatal sepsis, neonatologists predict clinical outcome based on the presence of riskfactors and nonspecific test results, before the clinical signs onset.…”
Section: Introductionmentioning
confidence: 99%